Pendampingan Perhitungan Joint Cost Pada Umkm Kirana Rotan Pekanbaru-Riau - Anne Mustika; Muhammad Ahyaruddin; Dian Puji Puspita Sari; Mentari Dwi Aristi; Della Hilia Anriva; Ilham Hudi (Asosiasi Dosen Akuntansi Indonesia, 2021)
Micro, Small and Medium Enterprises (UMKM) Rattan is a handicraft woven craft of the community which in its manufacture is still very simple and is often identified with things that are hereditary. Likewise, the recording and bookkeeping carried out by each transaction still uses traditional methods and does not separate costs between main products and byproducts, so the owner has difficulty in determining the profitability of each product. With the problems found, it is necessary to provide community service with training and mentoring using the method of calculating the cost of joint and side products. This service is important in the hope that there will be an increase in knowledge about joint cost calculations in order to determine which products are more profitable so that managers can formulate strategic policies.